Magnesium sulfate and brain in preeclampsia - Lacunza-Paredes, Rommel (2017)
Magnesium sulfate is the drug of choice in the prophylaxis and treatment of eclampsia. The recent understanding of the neurological manifestations within the reversible posterior leukoencephalopathy produced by preeclampsia has confirmed mechanisms that had been previously based on animal studies, thus adding value to this old drug. From the MAGPIE study to this day, many questions regarding the use of magnesium sulfate in preeclampsia remain ulsolved, but its value as a first-line treatment for brain manifestations in preeclampsia is undoubtedly high.